Development of a purified cholera toxoid. III. Refinements in purification of toxin and methods for the determination of residual somatic antigen. - Rappaport, R S (1976)
The addition of an ultrafiltration step to the purification procedures previously described for cholera toxin (Rappaport et al., (1974) permitted the preparation of highly purified antigenic toxoids essentially free of somatic antigen(s). The purity of such toxoids is established: (i) by the absence of more than about one part limulus amebocyte lysate (LAL)-positive endotoxin per 10(5) parts toxoid and (ii) by the inability of the toxoids to elicit a significant rise in rabbit vibriocidal antibody. The antigenicity of the toxoids is demonstrated by their ability to produce the same high levels of rabbit serum antitoxin as are produced by comparable toxoids containing small amounts of somatic antigen. The results also indicate that amounts of somatic antigen of the order of less than or equal to 1 mug/100 mug of toxoid do not exert an adjuvant effect on the toxoid, at least with respect to circulating antitoxin. Other data show that, where present, the ability of somatic antigen to elicit vibriocidal antibody is influenced by the immunization schedule employed and that a correlation exists between the LAL-determined endotoxin content of the toxoids and their ability to stimulate vibriocidal antibody. Somatic antigen-free toxoids, purified and tested by the refinements herein described, were prepared for use in the National Institutes of Health sponsored field trials, and data pertaining to their purity and antigenic properties are presented.